Optimization of xylonic acid production using recombinant e. coli bl21 (de3) with inserted gene from ralstonia pickettii - Nurul Atikah, Mohd Rodzri (2021)
ᴅ-Xylonic acid (XA) is a five-carbon sugar acid compound that has made the list of top 30 value-added chemicals from biomass with promising potentials. XA have similar properties as gluconic acid (GA) which is used in many different fields such as food, construction and textile industries. Production of GA however uses glucose as substrate therefore making its production competes with food production. With the increasing glucose price in the market, XA that is produced from non-food carbohydrate would be a valuable and cheaper substitute to GA. In recent years, XA is produced through microbial conversion of genetically engineered microorganism rather than extracting naturally oxidized XA from xylose. However, production of XA is yet to be produced at an industrial scale as the bio-based industry is still facing certain limitations such as low XA yield, slow production rate and certain bacterial species that produce XA requires complex growth medium. In this study, one-factor-at-a-time (OFAT) and central composite design (CCD) using Design Expert Software were employed to screen and optimize the effect of temperature, initial pH of medium and agitation rate on XA production from recombinant E. coli BL21 (DE3) fermentation in shake flask, followed by kinetic study using Leudeking-Piret equation to compare and evaluate XA production in shake flask and 2 L bioreactor fermentation. In screening, temperature, initial pH of medium and agitation rate were varied from 25°C to 40°C, pH 5.5 to pH 8.5 and 50 rpm to 250 rpm respectively. Meanwhile in optimization, process parameters were set at 35°C to 39°C, pH 6.5 to pH 7.5 and 150 rpm to 250 rpm which generated a total of 17 experiments with three centre points. Fermentation samples were analyse using Hydroxamate method and DNS method to determine XA and xylose concentration respectively. OFAT results show that the highest concentration of XA (9.82 ± 0.22 g/L) was obtained at 37°C, pH 7 and 200 rpm. Optimization results show that the developed quadratic model is fitted with the experimental data with R and R2 value of 0.9661 and 0.9333 respectively. The optimize condition for XA production were 36.8°C, initial pH of 6.8 and the agitation rate of 208 rpm. Concentration of XA as high as 11.15 ± 0.80 g/L was obtained when fermentation was governed under the optimize culture conditions. During fermentation in bioreactor using optimized parameters, XA production reduces to 6.89 g/L XA from 10 g/L xylose. This shows a 24% reduction of XA produced from fermentation in bioreactor compared to shake flask. Higher specific growth rate of recombinant E. coli BL21 (DE3) and higher concentration of XA was obtained by fermentation in shake flask which is 0.273 h-1and 9.06 g L-1 XA respectively. The kinetic study using Leudeking-Piret equation illustrates that XA is growth-associated product. Hence, to increase concentration of XA in bioreactor fermentation, recombinant E. coli BL21 (DE3)’s growth rate must also be increase. Overall, optimization process for temperature, pH and agitation rate had further increased XA from recombinant E. coli BL21 (DE3) by 13.5% higher compared to OFAT process. These results suggest a promising industrial-scale production of XA from recombinant E. coli BL21 (DE3) with inserted gene from Ralstonia pickettii.